The Headmaster-as-a-mentor: a Mentoring Model for Rural Primary School of Sarawak (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
: This paper attempts to present an alternative approach to training and improving the quality of teachers serving in rural schools of Sarawak. Based on the understanding that teacher training places are quite limited and that there are limited opportunities for meaningful interaction between school personnel and the central office or the teacher training institutions, it is argued that the overall quality of the teaching learning processes can be achieved through a systematic and properly structured school-based teacher training and guidance programme. A mentoring approach that places the headmaster as the mentor is viewed as a suitable alternative, as administratively and professionally it will have these merits: (a) It will provide the temporary teachers the opportunity to continue to serve in their respective schools, and at the same time receive some form of formal training and guidance; (b) It will allow for a better cooperation, collaboration and teamwork and greater sense of ownership among the school personnel and also between the school and the local education institution and the teacher training colleges; and (c) It will encourage greater staff professional growth as the mentors will also be gaining from the training they received to become effective mentors and from the actual process of guiding and helping the beginning and the temporary teachers under their care